2013
DOI: 10.3892/etm.2013.1095
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between serum high-mobility group box-1 levels and high-sensitivity C-reactive protein and troponin I in patients with coronary artery disease

Abstract: The aim of this study was to evaluate the correlation between levels of serum high-mobility group box-1 (HMGB1) and high-sensitivity C-reactive protein (hs-CRP) and cardiac troponin I in patients with coronary artery disease. The levels of serum HMGB1, hs-CRP and cardiac troponin I were measured in 98 patients with coronary artery disease and in 30 healthy subjects. The correlation between serum HMGB1 levels and hs-CRP and cardiac troponin I levels was analyzed. Serum HMGB1 levels in patients with coronary art… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
18
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 19 publications
(26 reference statements)
2
18
0
Order By: Relevance
“…Specific research on the cardiovascular system is still inconclusive. An interesting finding was that levels of HMGB1 in serum of MI patients are correlated with CRP and Troponin I levels [313]. Furthermore, Xu et al showed that HMGB1 plays a major role in I/R injury by working via TNF-α and the JNK signaling pathway, implying that the blockade of HMGB1 could yield cardioprotective effects [314].…”
Section: Pathophysiology Of the Inflammatory Response In Heart Failurementioning
confidence: 97%
“…Specific research on the cardiovascular system is still inconclusive. An interesting finding was that levels of HMGB1 in serum of MI patients are correlated with CRP and Troponin I levels [313]. Furthermore, Xu et al showed that HMGB1 plays a major role in I/R injury by working via TNF-α and the JNK signaling pathway, implying that the blockade of HMGB1 could yield cardioprotective effects [314].…”
Section: Pathophysiology Of the Inflammatory Response In Heart Failurementioning
confidence: 97%
“…12,32) Previous studies have shown that HMGB1 functions as a pro-inflammatory cytokine in certain cardiovascular diseases, and it was related to the severity of coronary artery disease. 33,34) Yao, et al demonstrated that myocardial expression of HMGB1 significantly increased in rats with acute MI. 35) High serum levels of HMGB1 may cause cardiac inflammation and left ventricular dysfunction after MI.…”
Section: Discussionmentioning
confidence: 99%
“…The first 40 peptide segments of B-box can induce the production of TNF-α and IL-6 [4]. As a pro-inflammation cytokine, HMGB1 takes an important role in many cardiovascular diseases, such as atherosclerosis, myocardial ischemia/reperfusion injuries, heart failure and myocardial infarction [5][6][7][8][9]. Recently, several studies showed that exogenous administration of HMGB1 after myocardial infarction or acute global I/R leads to the recovery of left ventricular function through the regeneration of cardiomyocytes.…”
Section: Contents Lists Available At Sciencedirectmentioning
confidence: 99%